Anthropogenic influences on annual flux of cations and anions at meio stream basin, São Paulo State, Brazil - Conceicao, F. T. [UNESP]; Sardinha, D. S. [UNESP]; Souza, A. D. G.; Navarro, G. R. B. [UNESP] (Springer, 2010)
The chemical dynamics at Meio Stream Basin, So Paulo State, Brazil were evaluated using major elements as natural tracers. The surface water samples from Meio Stream were collected near the mouth of Meio Stream at the confluence with the Mogi-Gua double dagger u River on February 25, 2005, April 20, 2005, and July 8, 2005. Rainwater samples were collected (using a "bulk" collector) for 1 year at one sampling point located about 4 km from downtown Leme city and other possible sources of contamination. The analyses were performed by pH, temperature, dissolved oxygen, electrical conductivity, total solids, sulfate, nitrate, phosphate, alkalinity, chloride, sodium, calcium, potassium, and magnesium. This basin has serious environmental problems in terms of rainwater and surface water quality, which result in the negative annual flux of cations and anions at Meio Stream Basin, with the exception of chlorine. The Meio Stream, downstream from Leme city, receives several elements/compounds through anthropogenic activities, mainly related to the discharge of domestic effluents. Anthropogenic inputs (mining, fossil fuel burning, and agricultural activities) are responsible for the higher concentrations of cations and anions in the rainwater from this basin.
Keywords: Chemical dynamics; Major ions; Watershed; Anthropogenic influences